FINANCIAL PERFORMANCE ANALYSIS USING EVA, MVA, AND FVA METHODS (CASE STUDY OF TELECOMMUNICATION SUB- SECTOR COMPANIES IN THE BEI KOMPAS100 INDEX FOR THE 2021-2023 PERIOD) - Rizky Tongian; Herman Karamoy; Victorina Z. Tirayoh (CV. RADJA PUBLIKA, 2025)
Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA) are methods of analyzing financial performance by looking at the value added after calculate all of capital cost. The purpose of this study is to analyze the financial performance using EVA, MVA, and FVA methods in telecomunication sub sector companies in the Kompas100 Index on the IDX for the 2021-2023 period. The research method used is qualitative descriptive. The sampling method used in this study is purposive sampling. A total of four telecomunication sub sector companies were used as sample. The result of the study indicates that with the use of EVA method, the companies tend to produce negative EVA result (EVA < 0). By using the MVA method, all the companies get positive MVA result (MVA > 0). By using the FVA method, all the companies also get positive FVA result (FVA > 0).